STRATEGY FOR BUILDING ACHIEVEMENT VILLAGES IN KUANTAN SINGINGI DISTRICT (CASE STUDY OF KOPUNG ISLAND VILLAGE) - Desriadi - (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
Building an outstanding village is an activity of cultivating the values and productivity of the village community. Because the values instilled help explore existing productivity values so that they can improve the quality of thinking and feeling, as well as psychological quality and productivity. In order to develop values, moral attitudes, understanding, skills, and productivity products which are very essential related to personal and social issues in integrity, it is needed by individuals, family members, workers as well as members of society and democratic citizens. Building an outstanding village is emphasized on values and morals as well as intelligence and productivity.